Mencari Murray Bookchin dalam Belantara Ilmu Sosial - Putra, Moch. Rizky Pratama (The Sociology of Islam, 2021)
This study discusses the metatheory of sociological paradigms as a method for finding and placing Murray Bookchin's concept of thinking based on the foundations of his thought, namely dialectical naturalism as philosophical basis and the concept of social ecology as praxis. This study uses library research approach, namely a comparative study to explore and discover Murray Bookchin's social ecology concepts in intersection with the sociological paradigm typology George Ritzer, Margaret Poloma, Gibson Burrel, and Gareth Morgan. Murray Bookchin, connect the social facts paradigm and social definitions in social science. Here lies the importance of the exemplar concept developed by Ritzer. First, the position of humans who are attached or deterministic due to the confinement of hierarchical social institutions causes them to accept the "nature" wherein they have to exploit nature as a form of existence and their way of fulfilling their false needs. Second, humans also have the freedom to use their mind as a support for non-human beings. Since non-human beings cannot formulate their own laws and norms, man plays the role as an extension of the tongue of the "mute" non-human being. This seeking process is a way to elaborate and offer the concept of social ecology as one of the important theories in social science. This is because the philosophy of dialectical naturalism, which from the very beginning was the starting point for Murray Bookchin interpreting the universe, has an important contribution in the social science dimensions, particularly sociology